Advances in Remediation of Contaminated Sites: Volume I - Lu, Guining; Diao, Zenghui; Huang, Kaibo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is of interest regarding contaminated sites remediation, which integrates the research results within 20 publications covering contaminated sites remediation's full life cycle. They include pollution investigation, environmental fate, pollution control, and review. In addition, the reprint addresses all aspects of contaminated site remediation, including heavy metal pollution, organic pollution, and combined pollution. These results can help to understand the remediation of the contaminated sites in depth throughout the life cycle and help break through the bottleneck of contaminated sites remediation and provide new ideas and methods for the development of contaminated sites remediation.